Hypertension, Chronic Kidney Disease, and Renal Pathology in a Child with Hermansky-Pudlak Syndrome - Roberto Gordillo; Marcela Del Rio; David B. Thomas; Joseph T. Flynn; Robert P. Woroniecki (International Journal of Nephrology)
We report a child with Hermansky-Pudlak Syndrome (HPS) and chronic kidney disease (stage II) with histological diagnosis of focal segmental glomerulosclerosis (FSGS). A 15-year-old male of Puerto Rico ancestry with history of HPS, hypertension (HTN), asthma, obesity, and chronic kidney disease (CKD) stage II presented with new-onset proteinuria without edema. His blood pressure had been controlled, serum creatinine had been 0.9–1.4 mg/dL, and first morning urine protein/creatinine ratio (UPC) ranged from 0.2 to 0.38. Due to persistent nonorthostatic proteinuria with CKD, renal biopsy was performed and FSGS (not otherwise specified) with chronic diffuse tubulopathy (tubular cytoplasmic droplets) and acute tubular injury was reported. Ceroid-like material is known to infiltrate tissues (i.e., lungs, colon, and kidney) in HPS, but the reason for the renal insufficiency is unknown. Nonspecific kidney disease and in one adult case IgA nephropathy with ANCA-positive glomerulonephritis have previously been reported in patients with Hermansky-Pudlak syndrome. To our knowledge, we report the first pediatric renal pathology case of HPS associated with CKD. This paper discusses presentation and management of renal disease in HPS.